Model Pemilihan Angkutan Sekolah : Studi Kasus Kawasan Kotabaru, Yogyakarta - Antonius Haryo I (Forum Teknik, 2003)
)Alumni  Jurusan Teknik Sipil Fakultas  Teknik  UGMSigit PriyantoJurusan Teknik  Sipil & Magister Sistem dan  Teknik  Transportasi  UGMAbstractWith  it's  title  as  a city of student,  Yogtakarta has  a large  amount  of students which  isaround  105,684  students,  Iiving  in  Yogtakarta  city.  Therefore,  it  was concluded  that  trafic  inYogtakarta  could be much influenced  by students. The  intention  of  this research  is  tounderstand  the  characteristics of students  traveling  with  private  cars, and  if  they  are offeredpublic  transportation  and  they  choose  it.  Therefore  the  congestion  can be reduced.The  stated preference  method  is  applied  to  this  study  to  investigate  the  response  of  privatecar  passengers  to  shift  in  public  transportation  in school  troveling.The  results  showe  that  if  the  public transport  is  available  they  may  be  choose  it  rather  thanprivate cars.Keywords:  public  transport,  private  car,  school  traveling